Aesthetic Transcendence: Fashion's Evolution, Philosophical Reflections, and Societal Impact - Sharma, Ankita (UIN Sunan Gunung Djati Bandung, 2024)
This research paper explores the evolution of fashion from its utilitarian origins over 170,000 years ago to its contemporary role as a symbol of cultural expression and individual identity. Tracing the historical trajectory through ancient civilizations, the Renaissance era, and significant societal shifts post-World War II, the study highlights the dynamic interplay between culture, external forces, and fashion. It also delves into the commodification of beauty in the contemporary era, examining the persuasive techniques used by beauty brands in advertisements, such as leveraging emotional states to connect deeply with consumers. The global impact of beauty standards and the perpetuation of white-centric ideals are scrutinized, emphasizing influential figures like Marcus Garvey, who challenged these norms. The study sheds light on the beauty industry's promotion of skin-lightening and hair-straightening products, particularly in Asian markets, and offers philosophical reflections on these beauty standards. Engaging with the works of Hume, Kant, Santayana, and Schiller, the paper dissects the subjective and objective dimensions of beauty, including Hume's emphasis on pleasure and pain, Kant's categorization of beauty, Santayana's concept of objectified pleasure, and Schiller's influence on German Idealism. It culminates with an exploration of Jean Baudrillard's